2018
DOI: 10.1371/journal.pone.0202023
|View full text |Cite
|
Sign up to set email alerts
|

“We might get a lot more families who will agree”: Muslim and Jewish perspectives on less invasive perinatal and paediatric autopsy

Abstract: BackgroundPerinatal and paediatric autopsy rates are at historically low levels with declining uptake due to dislike of the invasiveness of the procedure, and religious objections particularly amongst Muslim and Jewish parents. Less invasive methods of autopsy including imaging with and without tissue sampling have been shown to be feasible alternatives. We sought to investigate attitudes including religious permissibility and potential uptake amongst members of the Muslim and Jewish communities in the United … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 28 publications
7
44
0
Order By: Relevance
“…Our findings suggest that the MinImAL procedure has a performance similar to that of standard autopsy in terms of the proportion of IUFD/stillbirth cases in which a cause of death is determined. Given that recent data indicate that LIA techniques are well accepted by parents and religious communities, these findings have implications for perinatal autopsy practice globally, as acceptability of standard autopsy continues to decline.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings suggest that the MinImAL procedure has a performance similar to that of standard autopsy in terms of the proportion of IUFD/stillbirth cases in which a cause of death is determined. Given that recent data indicate that LIA techniques are well accepted by parents and religious communities, these findings have implications for perinatal autopsy practice globally, as acceptability of standard autopsy continues to decline.…”
Section: Discussionmentioning
confidence: 98%
“…This is likely to be because of the small number of Muslim and Jewish responders. However, qualitative research with parents and religious leaders from these two religious groups has shown that the invasiveness of standard autopsy is a key reason why Muslim and Jewish families decline, along with the requirement to bury the body quickly, and that non‐invasive approaches in particular, would be considered religiously permissible and much preferred …”
Section: Discussionmentioning
confidence: 99%
“…However, in this issue we hope to persuade you otherwise, as the contents of this special issue on ultrasound and genetic syndromes demonstrate how expert sonography and other fetal imaging is key to maximising the benefits of the technological advances we are seeing in molecular diagnosis. While largely focused on prenatal imaging, we also show how combined prenatal ultrasound and postnatal MRI examinations may be able to replace traditional post‐mortem examination, an approach welcomed by both the public and patients …”
mentioning
confidence: 81%